Onion anthocyanins: Extraction, stability, bioavailability, dietary effect, and health implications - Samota, Mahesh Kumar; Sharma, Madhvi; Kaur, Kulwinder; Sarita,; Yadav, Dinesh Kumar; Pandey, Abhay K.; Tak, Yamini; Rawat, Mandeep; Thakur, Julie; Rani, Heena (Frontiers in Nutrition, 2022)
Anthocyanins are high valued compounds and their use as functional foods and its natural colorant have potential health benefits. Anthocyanins seem to possess anti-oxidative properties which help to prevent neuronal diseases and thereby exhibit anti-inflammatory, chemo-therapeutic, cardio-protective, hepato-protective, and neuro-protective activities. They also shows different therapeutic effects against various chronic diseases. Anthocyanins are present in high concentration in onion. In recent years, although both conventional and improved methods have been used for extraction of anthocyanins, but now days the improved methods are of great importance because of higher yield and stability of anthocyanins. In this review we compile the anthocyanins and its derivatives found in onion and the factors affect their stability. We also analyze the different extractions techniquesof anthocyanins. From this point of view, it is very important to be precisely, aware of the impact that each parameter has on the stability and subsequently potentiate their bioavailability or beneficial health effects. We present an up-to date information on bioavailability, dietary effects and health implications of anthocyanins such as anti-oxidant, anti-diabetic, anti-cancerous, anti-obesity, cardio-protective, and hepato-protective activities.